Novel chemical kinetic mechanism for CFD simulation of hydrogen-enriched natural gas/diesel RCCI combustion - Fakhari, Amir Hossein; Salahi, Mohammad Mahdi; Gharehghani, Ayat; Hunicz, Jacek; Mikulski, Maciej; Andwari, Amin Mahmoudzadeh (Elsevier, 2025)
Reactivity Controlled Compression Ignition (RCCI) is a promising approach for decarbonizing marine engines by integrating green hydrogen into natural gas (NG) supply streams. This dual-fuel strategy improves efficiency and minimizes emissions. To simulate RCCI engines effectively, accurate chemical kinetic mechanisms tailored for internal combustion engines are crucial. This study develops a reduced mechanism with 60 species and 372 reactions, optimizing it for ignition delay time (IDT) and laminar flame speed (LFS). Laboratory tests validate the mechanism, showing a 20% improvement in IDT prediction accuracy over existing NG-diesel models, with simulation errors reduced to 0.2 ms. CFD simulations using the mechanism evaluate H₂-enriched NG RCCI combustion, revealing that small-scale H₂ addition enhances combustion efficiency by reducing methane slip and CO emissions. A 30% H₂ substitution (energy ratio) improves combustion efficiency by 3%, despite a 50% increase in NOx emissions, which remain under 93 ppm. This study proposes a novel mechanism for RCCI combustion simulations, enhancing predictive accuracy and revealing key benefits of H2-enriched NG combustion.
Keywords: RCCI combustion; CFD; Hydrogen-enriched natural gas; Reaction mechanism validation; fi=Energiatekniikka|en=Energy Technology|